Multi‐terminal medium voltage DC grids fault location and isolation. Issue 14 (1st November 2016) - Monadi, Mehdi; Koch‐Ciobotaru, Cosmin; Luna, Alvaro; Ignacio Candela, Jose; Rodriguez, Pedro
Abstract : Voltage source converters (VSCs) are highly vulnerable to DC fault current; thus, protection is one of the most important concerns associated with the implementation of multi‐terminal VSC‐based DC networks. This study proposes a protection strategy for medium voltage DC distribution systems. The strategy consists of a communication‐assisted fault location method and a fault isolation scheme that provides an economic, fast and selective protection by means of using the minimum number of DC circuit breakers. This study also introduces a backup protection which is activated if communication network fails. The effectiveness of the proposed protection strategy is analysed through real‐time simulation studies by use of the hardware‐in‐the‐loop approach. Furthermore, the effects of fault isolation process on the connected loads are also investigated. The results show that the proposed strategy can effectively protect multi‐terminal DC distribution networks and VSC stations against different types of faults.